Global Enterprise Management, Volume I New Perspectives on Challenges and Future Developments - Camillo, A.; Camillo, A. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Global Enterprise Management unites theory, academic knowledge, and practitioner experience to provide students, educators, and practitioners with the skills to succeed in the global managerial landscape.